The Effects of Zinc Supplementation on Immune Response of Obese Children With Family History of Atopy - W Wistiani; Dewi Ratih; M Mulyono; Saekhol Bakri (Journal of Biomedicine and Translational Research, 2018)
Introduction: Obesity is associated with low-grade chronic inflammation and disbalance between cytokine production of T helper1 and T helper2 cells.  Zinc plays role in balancing immune response, has anti-oxidant and anti-inflammation activities; its deficiency also common in obesity.  The role of zinc supplementation in children with obesity with risk of atopy needs to be elucidated.Materials and Method: We performed randomized controlled trial double-blind to investigate the effect of daily 15 mg zinc supplementation for 6 weeks in children aged 13 to 14 years old with obese who has family history of atopy.  Subjects were divided into group of zinc supplementation and placebo, recruited from junior high schools from Semarang municipality, performed during periods from January to December 2013.  Plasma zinc concentration, leptin, immunoglobulin-E (Ig-E), interferon-γ (IFN-γ), interleukin-4 (IL-4) were measured, also body weight, height and ISAAC questionnaire to recruit subjects with family history of atopy.Result: There were 36 subjects.  The concentration of zinc serum, Ig-E, IFN-γ, and IL-4 of two groups before supplementation were not significantly different (p>0.05).  Zinc supplementation increase the mean level of zinc concentration on treatment group compare to placebo group (27.74+11.80 vs 3.47+2.55, p=0.000).  The concentration of Ig-E, IFN-γ and IL-4 serum were decreased at treatment group (15.5+20.46 vs 20.02+38.02, p=0.613), (1.82+3.59 vs 0.911+3.51, p=0.174), and (4.76+6.49 vs 2.44+4.41, p=0.085) respectively.  Conclusion: Zinc supplementation increased the level of zinc serum concentration of obese children and decreased the risk of atopy.